Loss of p53 function promotes DNA damage-induced formation of nuclear actin filaments - Takeru Torii; Wataru Sugimoto; Katsuhiko Itoh; Natsuki Kinoshita; Masaya Gessho; Toshiyuki Goto; Ikuno Uehara; Wataru Nakajima; Yemima Budirahardja; Daisuke Miyoshi; Takahito Nishikata; Nobuyuki Tanaka; et al. (Cell Death and Disease, 2023)
Abstract Tumor suppressor p53 plays a central role in response to DNA damage. DNA-damaging agents modulate nuclear actin dynamics, influencing cell behaviors; however, whether p53 affects the formation of nuclear actin filaments remains unclear. In this study, we found that p53 depletion promoted the formation of nuclear actin filaments in response to DNA-damaging agents, such as doxorubicin (DOXO) and etoposide (VP16). Even though the genetic probes used for the detection of nuclear actin filaments exerted a promotive effect on actin polymerization, the detected formation of nuclear actin filaments was highly dependent on both p53 depletion and DNA damage. Whilst active p53 is known to promote caspase-1 expression, the overexpression of caspase-1 reduced DNA damage-induced formation of nuclear actin filaments in p53-depleted cells. In contrast, co-treatment with DOXO and the pan-caspase inhibitor Q-VD-OPh or the caspase-1 inhibitor Z-YVAD-FMK induced the formation of nuclear actin filament formation even in cells bearing wild-type p53. These results suggest that the p53-caspase-1 axis suppresses DNA damage-induced formation of nuclear actin filaments. In addition, we found that the expression of nLifeact-GFP, the filamentous-actin-binding peptide Lifeact fused with the nuclear localization signal (NLS) and GFP, modulated the structure of nuclear actin filaments to be phalloidin-stainable in p53-depleted cells treated with the DNA-damaging agent, altering the chromatin structure and reducing the transcriptional activity. The level of phosphorylated H2AX (γH2AX), a marker of DNA damage, in these cells also reduced upon nLifeact-GFP expression, whilst details of the functional relationship between the formation of nLifeact-GFP-decorated nuclear actin filaments and DNA repair remained to be elucidated. Considering that the loss of p53 is associated with cancer progression, the results of this study raise a possibility that the artificial reinforcement of nuclear actin filaments by nLifeact-GFP may enhance the cytotoxic effect of DNA-damaging agents in aggressive cancer cells through a reduction in gene transcription.